On making choices: some thoughts on an ethnographic film screening - Sampaio, S.; Martins, H.; Salgado, R.S.; Schefer, R. (XIV Congreso de Antropología de la FAAEE: “Antropologías en transformación: sentidos, compromisos y utopías”, 2017)
In this paper we describe, analyse and reflect on our first-hand experiences as members of the jury of the Ethnographic Film Screening of the 6th Meeting of the Portuguese Anthropological Association (APA), which took place in the University of Coimbra, in June 2016 (http://vicongresso.apantropologia.org/mostra-de-filme-etnografico/). To quote from our call for the ethnographic films, our “simple invitation” was to “show through images how ‘Disputed Futures’ [the topic of the general meeting] mean the diversity of presents and pasts; because the world is made on different rhythms, impulses, desires towards the uncertainty and incompleteness of history.” Our criteria for the film selection process was divided into (1) cinematic quality and originality (cinematography, sound, etc.) and (2) the anthropological character of the films. In the end, we selected 21 out of a total number of 101 films received, among short, medium and feature-length formats. The selection proved a difficult process, raising important issues, namely: was this ‘practical’ division between ‘cinematic quality’ and ‘anthropology’ theoretically (and even empirically) sound? Was it able to overcome the separation between content and form? To what extent were our preferences determined by our different professional backgrounds? Is it possible to assess fairly the ‘ethnographicity’ of such a large number of films, originating from a wide range of geographical and even academic contexts? How did the context of the event – a meeting of anthropologists – impact on our viewings and final choices? Lastly, how did the cinema-going conventions and expectations associated with this kind of film exhibition frame constrain the films’ ‘ethnographicity’? Are there any exhibition alternatives?